European System of Financial Supervision as an institution providing consumers protection - Krzak, Karolina (Journal of Finance and Financial Law, 2019)
The purpose of this article is to analyze of the organization and operation of the European System of Financial Supervision – an institution that ensures trust in the financial system as a whole and adequate protection of consumers. The autor decided to analyze the statement that European System of Financial Supervision is an appropriate institution that does not require changes, which provides consumers with adequate protection.